Development Writing Text Module Based on Project Based Learning Through Exploring Local Wisdom of Kediri Residency for Elementary School Teacher Education’s Students - Endang Sri Mujiwati; Rian Damariswara; Karimatus Saidah (STAI Hubbulwathan Duri, 2022)
Writing is the way to express the idea according to the author knowledge, By writing, students can exercise their writing ability according to their interest in educational themes but Pre eliminary research on elementary school teacher education student in a university of Kediri show that students in the Language Studies course have obstacles in understanding various text materials like difficulty mentioning the variety of texts and difficulty identifying the structure of each variety of text.The purpose of developing the various type of text module is first to describe the module development procedure based on the ADDIE development model, second to describe the validity of the module based on the assessment of Indonesian language experts, and third to find out whether the module is practical for use by elementary school teacher education program students. The development method uses the ADDIE model, the research subjects are elementary school teacher education students at the University in Kediri class of 2020. The data analysis technique used is descriptive quantitative to describe the data in the form of questionnaire scores of validity and practicality, and descriptive qualitative to describe the data in the form of suggestions and comments and observations during the implementation process. The results showed that the module developed was declared very valid by Indonesian language experts with a score of 95.6% and was stated to be very practical according to the results of the practicality questionnaire distributed to students with a score of 86.7%.